2015
DOI: 10.4218/etrij.15.2314.0059
|View full text |Cite
|
Sign up to set email alerts
|

Generation Expansion Planning Model Supporting Diverse Environmental Policies for Reduction of Greenhouse Gases

Abstract: The purpose of this paper is to a develop model for generation expansion planning that can support diverse environmental policies for the reduction of greenhouse gases (GHGs) of South Korea. South Korea is required to reduce its GHG emissions by 30% from the BAU level by 2020. The Wien Automatic System Planning Package currently used in South Korea has limitations in terms of the application of renewable energy policies and GHG targets; this paper proposes the use of an equipment planning model named generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…At the 21st Conference of the Parties, which was held in Paris from November 30 to December 11 2015, representatives from all over the world announced targets to reduce greenhouse gas emissions and curtail climate change. The reduction of greenhouse gases aimed by the Paris agreement is related to fossil-fuel oriented energy consumption based on the continuing trends of rising energy demand [1]. For example, the electricity demand and consumption in the U.S. have increased 2.5% annually over the last 20 years [2].…”
Section: Introductionmentioning
confidence: 99%
“…At the 21st Conference of the Parties, which was held in Paris from November 30 to December 11 2015, representatives from all over the world announced targets to reduce greenhouse gas emissions and curtail climate change. The reduction of greenhouse gases aimed by the Paris agreement is related to fossil-fuel oriented energy consumption based on the continuing trends of rising energy demand [1]. For example, the electricity demand and consumption in the U.S. have increased 2.5% annually over the last 20 years [2].…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al [19] developed a numerical model of reducing GHG in South Korea for power expansion planning to support various environmental policies. The authors identified 36% of GHG could be reduced far over 30% of the 2020 reduction target.…”
Section: Previous Researchmentioning
confidence: 99%